An economic evaluation of invasive alien plant control programmes in the mountain catchment areas of the Western Cape Province, South Africa - Marais, Christo (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1998.